2015
DOI: 10.5860/crl.76.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Evidence Use in Academic Librarian Decision Making

Abstract: The objective of this qualitative study was to identify and explain challenges encountered by academic librarians when trying to incorporate evidence into their practice. The findings resulted in the identification of five main determinants that act as either obstacles or enablers of evidence use. The identification of these determinants provide librarians with a greater understanding of the complex processes and individual as well as organizational factors that impact decision-making processes within academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…The findings of this study also reflect the literature of Denise Koufogiannakis, 63 as well as that of Peter Hernon, Robert Dugan, and Joseph Matthews, 64 concerning evidence-based library and information practice (EBLIP). Hernon, Dugan, and Matthews state that EBLIP includes the following steps: asking a relevant question and then "gathering evidence; appraising the validity, reliability, and applicability of that evidence; applying the evidence to a decision; and evaluating the impact of the decision."…”
Section: Applying the Theory Of Academic Library Strategic And Cultursupporting
confidence: 83%
“…The findings of this study also reflect the literature of Denise Koufogiannakis, 63 as well as that of Peter Hernon, Robert Dugan, and Joseph Matthews, 64 concerning evidence-based library and information practice (EBLIP). Hernon, Dugan, and Matthews state that EBLIP includes the following steps: asking a relevant question and then "gathering evidence; appraising the validity, reliability, and applicability of that evidence; applying the evidence to a decision; and evaluating the impact of the decision."…”
Section: Applying the Theory Of Academic Library Strategic And Cultursupporting
confidence: 83%
“…"Evidence-based practice is relevant to all sizes of libraries and may be even more applicable to libraries staffed by one person." Koufogiannakis, 2015;Partridge, Edwards, & Thorpe, 2010) There is no one right way to do or be evidence-based. The way evidence-based practice is applied in a library is up to the individual library professional.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown that librarians are sensitive towards micro-managing (meaning that library's top management is being over-controlling) and library leadership plays a vital role in the general organizational culture (Koufogiannakis, 2015). The key element in change management and strategic planning in academic libraries relies heavily on the directors of these libraries and often on their leadership skills and willingness to make tough choices.…”
Section: Liber Quarterly Volume 28 2018mentioning
confidence: 99%